The impact of top executive gender on asset prices: Evidence from stock price crash risk - Li, Yiwei; Zeng, Yeqin (Journal of Corporate Finance, 2019)
We examine the implication of executive gender on asset prices. Using a large sample of US public firms during 2006–2015, we find a negative association between female CFOs and future stock price crash risk. However, the impact of female CEOs on crash risk is not statistically significant. The results support the notion that CFOs play a stronger role than CEOs in curbing bad news hoarding activities because CFOs' primary duties are financial reporting and planning. Our findings are robust to several econometric specifications controlling for potential endogeneity and to alternative measures of crash risk. At last, we show that the negative relation between female CFOs and future stock price crash risk is more pronounced among firms with weaker corporate governance, less market competition, lower analyst coverage, and higher financial leverage. Collectively, our evidence highlights the importance of CFO gender for firm financial decision making and stock return tail risk.